Correlation Between History of ISTC Training on Independent Practicing Doctor With Discovery of TB Suspected Children in Surabaya City - Jatu, Madu Puspita Nuansa; Syahrul, Fariani (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
The burden of Tuberculosis in children cases in the world is unknown due to the lack of diagnostic tools that are